2022
DOI: 10.1155/2022/2112956
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Potential of Aqueous Extract of Fumaria indica on Isoproterenol-Induced Myocardial Infarction in SD Rats

Abstract: Ischemic heart disease (IHD) treatments and preventions by using plant extract and its phytochemical constituents have achieved considerable attention globally due to its cardioprotective effects. This study is aimed at investigating the cardioprotective and vascular effects of Fumaria indica (F. indica) crude extract on isoproterenol- (ISO-) induced myocardial infarction (MI) in Sprague-Dawley (SD) rats. Rats treated with isoproterenol (85 mg/kg, s.c), administered. Twice at an interval of 24 h showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…With GC pretreatment, the reduced cardiac troponin I level indicated that the hearts were well protected against ISO-induced MI and its related damage. These findings are in agreement with the studies on the cardioprotective effect of Fumaria indica , bergapten, and Curcuma longa ( Nahar and Akhter, 2018 ; Sajid et al, 2022 ; Yang et al, 2022 ). The increase in heart rate, prolonged QRS and QT interval, pronounced ST elevation, and shortened R-R interval and P- duration in the ECG of the ISO group reflected the presence of infraction, improper conduction of electrical impulses throughout cardiac tissues, AV node, and an overall cumulative cardiotoxic effect of isoproterenol ( Boarescu et al, 2019 ; Bocsan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With GC pretreatment, the reduced cardiac troponin I level indicated that the hearts were well protected against ISO-induced MI and its related damage. These findings are in agreement with the studies on the cardioprotective effect of Fumaria indica , bergapten, and Curcuma longa ( Nahar and Akhter, 2018 ; Sajid et al, 2022 ; Yang et al, 2022 ). The increase in heart rate, prolonged QRS and QT interval, pronounced ST elevation, and shortened R-R interval and P- duration in the ECG of the ISO group reflected the presence of infraction, improper conduction of electrical impulses throughout cardiac tissues, AV node, and an overall cumulative cardiotoxic effect of isoproterenol ( Boarescu et al, 2019 ; Bocsan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…The increase in heart rate, prolonged QRS and QT interval, pronounced ST elevation, and shortened R-R interval and P- duration in the ECG of the ISO group reflected the presence of infraction, improper conduction of electrical impulses throughout cardiac tissues, AV node, and an overall cumulative cardiotoxic effect of isoproterenol ( Boarescu et al, 2019 ; Bocsan et al, 2021 ). GC pretreated groups showed marked improvement in their ECG parameters, further providing evidence favoring its protective effect, and these detailed changes in ECG are in agreement with the earlier reports of ( Jain et al, 2018 ; Boarescu et al, 2019 ; Bocsan et al, 2021 ; Sajid et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…MDA, a major metabolite of oxidative free radicals, reflects the degree of peroxidation of myocardial tissue. And SOD as a vital antioxidant enzyme can improve myocardial oxidative stress injury by scavenging oxygen free radicals [ 6 , 37 ]. AEBA significantly decreased the content of MDA and increased the serum SOD activity, which might contribute to its effects on alleviating the injury degree of inflammation and fibrosis of the heart tissue in ISO-induced MI rats.…”
Section: Discussionmentioning
confidence: 99%
“…indica has been used in alternative medicine for decades to treat cardiovascular diseases, including hypertension. Reportedly, it possesses hepatoprotective properties, spasmolytic and spasmogenic, antileishmanial, antidiabetic, antianxiety, cognitive modulating activity, gastroprotective, anti-inflammatory, chemoprotective activity, antidengue, and antioxidant activity. , Predominantly, isoquinoline alkaloids are responsible for these actions, with protopine being the most commonly discovered . Previous research has demonstrated that protopine contains hypotensive properties, smooth muscle relaxants, and antiarrhythmic effects. , However, hydromethanolic extract of F. indica research on hypertension and myocardial ischemia is lacking in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“… 39 Previous research has demonstrated that protopine contains hypotensive properties, smooth muscle relaxants, and antiarrhythmic effects. 27 , 40 However, hydromethanolic extract of F. indica research on hypertension and myocardial ischemia is lacking in the scientific literature. Moreover, scientific facts supporting traditional usage and toxicity assessments of medicinal herbs persisted despite their increasing popularity and ubiquity.…”
Section: Introductionmentioning
confidence: 99%